(untitled) - Prothero, Donald R. (McGraw-Hill, 2004)
Evolution of the Earth reveals the logical framework of geology, shows relations of the science to the totality of human knowledge, and gives some idea of what it is to be a participant in the discipline. In keeping with the preference for a "How do we know?" rather than "What do we know?" approach, the authors stress what assumptions are made by earth historians, what kinds of evidence (and tools for gathering that evidence), and what processes of reasoning and limitations of hypotheses are involved in reconstructing and interpreting the past.
Keywords: Historical geology,Lịch sử địa chất